Association Between Nutrition-related Intentions and Food Selections Among Food Pantry Clients in Baltimore City (P04-046-19). (13th June 2019) - Gu, Yuxuan; Yan, Sally; Gunen, Bengucan; Poirier, Lisa; Ali, Shahmir; Adams, Lindsay; Craig, Hope; Gittelsohn, Joel
Abstract: Objectives: Ten % of low-income households in Baltimore rely on food pantries for long-term hunger relief. Although behavioral intentions have been shown to be associated with food choices in many settings, little is known about the relationship between pantry client food selections and their nutrition-related intentions. This study aims to address this gap to inform social and behavior change interventions in food pantries. Methods: Data was collected from 74 clients of 7 food pantries in Baltimore between September and October 2018. The overall nutritional quality of the foods received was measured using the Food Assortment Scoring Tool (FAST), with a higher score indicating a greater proportion of healthy foods. Client nutrition-related intentions were assessed via a survey. Three additive scales were created from the survey: how many days clients are most likely to try to eat healthier, to cook, and to cook with a kid in an average week in the last six months. We explored the association between clients' nutrition-related intentions and their average FAST scores and average client bag Gross Weight Share (GWS) of various food groups. Results: On average, the FAST score of client food bags was 63.0 ± 10.4. About half of the clients did not intend to eat healthier ( n = 40) or cook ( n = 37) on any days of an average week. On average, clients who intended to eat healthier had a score of 63.1 ± 11, compared to 62.97 ± 9.96 among those who did not. Clients who intended to cook had a score of 62.64 ± 11.57, compared to 63.45 ± 9.18 among those who did not. Clients who intended to cook with a kid had a score of 63.25 ± 13.98, compared to 63 ± 9.59 among those who did not. In terms of specific food groups, clients who intended to eat healthier and cook had a higher GWS of fresh fruits and vegetables, while clients who did not intend to cook or cook with a kid had a higher GWS of high-processed meat. These relationships were not statistically significant. Conclusions: We did not find that clients' nutrition-related intentions are associated with the healthfulness of the foods they select. Resources directed at improving food pantries might be better directed at improving access to healthier foods, as opposed to intentions regarding these foods. Funding Sources: Johns Hopkins University Lerner Center for Public Health Promotion.